Iatrogenic Perforations During Colonoscopy In a Portuguese Population: A Study Including In and Out-Of-Hospital Procedures - Campos,Sara (2016)
Introduction: The risk of iatrogenic perforations in colonoscopy is not negligible. Experience with endoscopic closure of perforations is increasing and new devices for this purpose are being released, making endoscopy a therapeutic option. National data regarding iatrogenic perforations is scarce and the burden of iatrogenic perforations in out-hospital procedures is poorly characterized in the literature. Objective: Evaluation of iatrogenic perforations rate during colonoscopy, their characteristics, management and prognosis. Methods: Retrospective study of all patients with perforations secondary to in-hospital and non-hospital colonoscopies treated in a tertiary hospital between 01-01-2006 and 01-10-2014. Demographic, endoscopic, radiological and therapeutic data were analyzed. Results: Fifty-three perforations were identified, 20 occurring in colonoscopies performed in non-hospital environment (45% with therapeutic procedures) and 33 occurring in-hospital procedures (73% in therapeutic colonoscopies; representing 0.12% of all colonoscopies carried out in-hospital). Patients: male in 56%, average age of 71 years, history of previous abdominopelvic surgery in 31% and diverticulosis in 10%. Colonoscopy: elective in 93%, under deep sedation in 21%, with less than excellent/good bowel preparation in 56%. A resident was the first performer in 10 cases. Perforations: average size of 21 mm (4-130 mm), diagnosed during the procedure in 51% of cases and occurred in rectum-sigmoid transition in 58.5%. Regarding therapeutics, all patients with perforation occurring in non-hospital colonoscopies were managed by surgery. Concerning treatment of those in our unit: 2-conservative, 12-endoscopic (10 successfully), 21-surgical (including the 2 cases with failure of the endoscopic approach). Comparing endoscopic treatment (n = 10, G1) versus surgery (n = 21; G2): perforation size - 9 mm (G1) versus 28 mm (G2); perforation location - 7/10 in rectum-sigmoid (G1) versus 8/21 in rectum-sigmoid and 10/21 transverse/ascending colon/hepatic angle (G2). Morbidity: 1 infection in G1 and 13 complications in G2 (infection, hemorrhage, fistula). Mortality: no deaths in G1 and 2 deaths at 30 days due to septic shock in G2. Conclusion: Perforations in colonoscopy are rare in our clinical practice. Endoscopic closure was effective, though limited to perforations found during the procedure. The mortality was relatively low and endoscopic management did not seem to worsen it. An additional effort is necessary in order to detect perforations during colonoscopy.